Practices of Buying Chicken According to Imam Syafi'i's Views in Traditional Markets - Indriyani, Seifita; daud, Daud (CV. Zabags Qu Publish, 2024)
Buying and selling is the exchange of goods or objects with agreements or conditions that have been agreed upon. In this buying and selling there are conditions and pillars that must be carried out, there are also provisions for the conditions themselves according to the imams, one of whom is Imam Shafi'i. This research discusses the practice of buying and selling broiler chickens according to the views of Imam Syafi'i in traditional markets (Case Study of Pandan Jaya Village, Geragai District, East Tanjung Jabung District). The problem in this research is first, what is the practice of buying and selling broiler chickens in the traditional market in Pandan Jaya Village? second, what is Imam Syafi'i's view of the practice of buying and selling broiler chickens? The method used in this research is a qualitative method with a case study approach. The data collection methods used were observation, interviews and documents and data sources were obtained from primary and secondary data. The results of this research are that the buying and selling practices that occur in the traditional market of Pandan Jaya Village in transactions do not have a feeling of mutual liking or sincerity, this is due to fraud and the attitudes of both parties (seller and buyer). Imam Syafi'i's views of the practice of buying and selling broiler chickens states that buying and selling is permitted, then he explained that there are pillars and conditions that must be met. Meanwhile, there is one pillar that is not fulfilled, namely the contract (ijab qabul) which is not carried out consensually or sincerely.